Triple dissociation of attention and decision computations across prefrontal cortex - Hunt, L; Malalasekera, N; De Berker, A; Miranda, B; Farmer, S; Behrens, T; Kennerley, S (Springer Nature, 2018)
Naturalistic decision-making typically involves sequential deployment of attention to choice alternatives to gather information before a decision is made. Attention filters how information enters decision circuits, implying attentional control may shape how decision computations unfold. We recorded neuronal activity from three subregions of prefrontal cortex (PFC) while monkeys performed an attention-guided decision-making task. From the first saccade to decision-relevant information, a triple dissociation of decision- and attention-related computations emerged in parallel across PFC subregions. During subsequent saccades, orbitofrontal cortex activity reflected value comparison between currently and previously attended information. By contrast, anterior cingulate cortex carried several signals reflecting belief updating in light of newly attended information, integration of evidence to a decision bound, and an emerging plan for what action to choose. Our findings show how anatomically dissociable PFC representations evolve during attention-guided information search, supporting computations critical for value-guided choice.